Acridinyl methyl esters as photoactive precursors in the release of neurotransmitter amino acids - Piloto, Ana M. (2013)
An investigation of the use of an azaheterocycle, acridine, as an alternative photochemically removable protecting group for the carboxylic function of neurotransmitter amino acids was carried out. 9-Bromomethylacridine was used in the reaction with glycine, alanine, glutamic acid, β-alanine and γ-aminobutyric acid, to obtain model ester derivatives, which were irradiated at different wavelengths in a photochemical reactor. The process was followed by HPLC/UV, resulting in the release of the active molecule in short irradiation times. The results obtained using 419 nm irradiation show promise (35-98 min) for practical purposes. The compounds were further characterised via time-resolved fluorescence to elucidate their photophysical properties and determine the decay kinetics.